Inactivation of the Medial Prefrontal Cortex Interferes with the Expression But Not the Acquisition of Diff erential Fear Conditioning in Rats - Lee, Yeon Kyung; Choi, June-Seek (Experimental neurobiology, 2012)
The medial prefrontal cortex (mPFC) has been implicated in the processing of emotionally significant stimuli, particularly the inhibition of inappropriate responses. We examined the role of the mPFC in regulation of fear responses using a diff erential fear conditioning procedure in which the excitatory conditioned stimulus (CS+) was paired with an aversive footshock and intermixed with the inhibitory conditioned stimulus (CS-). In the fi rst experiment, using rats as subjects, muscimol, a gamma-amino-butyric acid type A (GABAA) receptor agonist, or artifi cial cerebrospinal fl uid (aCSF) was infused intracranially into the mPFC across three conditioning sessions. Twenty-four hours aft er the last conditioning session, freezing response of the rats was tested in a drug-free state. Neither the muscimol nor the aCSF infusion had any eff ect on diff erential responding. In the second experiment, the same experimental procedure was used except that the infusion was made before the testing session rather than the conditioning sessions. Th e results showed that muscimol infusion impaired diff erential responding: the level of freezing to CS- was indiscriminable from that to CS+. Taken together, these results suggest that the mPFC is responsible for the regulation of fear response by inhibiting inappropriate fear expressions. KCI Citation Count: 0